Outbreak culture the Ebola crisis and the next epidemic - Sabeti, Pardis, 1975- (Harvard University Press, 2018)
An award-winning genetic researcher and a tenacious journalist examine each phase of the Ebola epidemic in West Africa, the largest and deadliest of its kind. Their postmortem identifies factors that kept key information from reaching doctors, complicated the government's response to the crisis, and left responders unprepared for the next outbreak.--